AI vs AI: The Internal Auditor in the Battle of the Artificial Intelligence Era - Nurul Fadhilah Farid (JRAK (Jurnal Riset Akuntansi dan Bisnis), 2025)
The digital era has significantly transformed internal audit practices, particularly with the growing presence of Artificial Intelligence (AI) across various business processes. This article discusses the challenges faced by internal auditors in dealing with AI as both a tool and an audit subject. This study uses a quantitative approach by distributing questionnaires to 120 internal auditors working in public and private sector organizations. The results reveal that understanding AI technology, auditor adaptability, and organizational support significantly affect internal audit effectiveness in the AI era. The findings highlight the need to develop auditors' capabilities in comprehending AI systems and the urgency of establishing audit frameworks responsive to technological dynamics